Multiproxy study of plant remains from Cerro Casa de Piedra 7 (Patagonia, Argentina). (10th January 2018) - Caruso Fermé, Laura; Velázquez, Nadia J.; Martínez Tosto, A. Cecilia; Yagueddú, Cristina; Burry, L. Susana; Civalero, M. Teresa
Abstract: The objective of this work is to carry out an integral study of macro and microbotanical remains with the aim of providing information to the palaeoenvironmental reconstruction and understanding the different practices employed in the acquisition of woody material used by hunter-gatherer societies from the northwestern region of the Santa Cruz Province, Argentine Patagonia, during the early and middle Holocene. For this purpose, we study macrobotanical remains (carbonized and non-carbonized wood) recovered from different combustion structures and from the sediment of the three stratigraphic levels dated by 14 C and resulting in ages of 9640 ± 190 years BP; 8380 ± 120 years BP and 6150 ± 105 years BP, of the Cerro Casa de Piedra 7 site. Also, pollen and small plant fragments of human and camelid coprolites were studied. The analysis conducted show differences in the taxonomic resolution obtained by each one of the proxies. The marked representation of Nothofagus pumilio among charcoal and wood makes clear that the forest was an environment recurrently used by hunter-gatherers occupying CCP7. The study of pollen and plant fragments coming from coprolites, allowed the identification of grass species typical of the steppe environments and forest-steppe ecotonal areas. In this way, plant fragments provide higher level of taxonomic resolution and a greater diversity for paleoenvironmental reconstruction. The results obtained by means of the multi-proxy analysis allowed us not only to enlarge the reconstruction of the hunter-gatherers livable environment, but also to recognize the availability and use of the plant resources in the Early-Mid-Holocene in the region.